Exploring Normalization of Deviance among Perioperative Registered Nurses in the Operating Room. (February 2022) - Wright, M. Imelda; Polivka, Barbara; Clark, Paul
Normalization of deviance is a phenomenon in which individuals and teams deviate from what is known to be an acceptable performance standard until the adopted way of practice becomes normalized. In health care, this phenomenon erodes the safety culture, and it can be particularly concerning in high-risk work environments, such as the operating room (OR). The purposes of this study were to: (a) Explore the concept of normalization of deviance in the OR; (b) Identify reasons for normalization of deviance; and (c) Identify factors that protect against normalization of deviance. This focused ethnographic study included a sample of 10 perioperative nurses who were interviewed. Our findings demonstrated that normalization exists in the OR. Reasons for normalization of deviance included productivity pressures, generalized complacency, complacency related to length of experience, social pressures, and negative acculturation. Factors that protect against normalization of deviance included nurse engagement and having supportive managerial relationships.